B.S. Patil's building and engineering contracts - Patil, B. S. (Bajirao Shankarrao), 1939-; Woolhouse, Sarita Patil (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"From the standpoint of practicing engineers, architects and contractors, the law of contract is the most important one and, from preparation of technical documents to its execution and in the determination of disputes, the engineer or architect must have relevant knowledge. This book acts as a practical guide to building and engineering contracts, to engineers, architects and contractors wherein all points are explained with illustrations gathered from decided court cases. This book covers the substantive law of contract applicable to building and engineering contracts with updated noteworthy judgements. FIDIC conditions are mentioned at appropriate places with a global focus"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Construction contracts -- India; Engineering contracts -- India